Assessing future maize water demand in Karnataka under CMIP6 climate projections: model evaluation and CROPWAT simulations - Shankarappa Sridhara; Hemareddy Thimmareddy; Mahesh Haroli; Santanu Kumar Bal; Bappa Das; Prakash Kumar Jha; P.V.Vara Prasad (Agricultural Water Management)
ABSTRACT: Maize is a crucial crop for food security and economic resilience, playing a significant role in agri-food systems. However, climate change poses increasing challenges to its cultivation, particularly by affecting water availability and crop water requirements. Climate projections indicate that increasing temperatures and changing rainfall patterns will alter crop evapotranspiration (ETc) and maize water demands. To assess future climate impacts, four CMIP6 models (ACCESS-ESM1–5, CNRM-ESM2–1, EC-Earth3-Veg-LR and MIROC6) were validated against IMD gridded data (1985–2014). Among these, ACCESS-ESM1–5 demonstrated the best performance for Karnataka and was selected for projection studies. Projections suggest that average minimum and maximum temperatures in Karnataka may rise by approximately 2°C and 1.5°C, respectively, in the near future. Using the CROPWAT model, kharif maize water requirements were estimated for various future periods. Results indicate a 3.6 % decrease in ETc and a 9.6 % increase in effective rainfall during near future (2024–2050) compared to baseline (1994–2023) under SSP245 scenario. However, ETc remains relatively stable for the mid-future (2051–2075) and far-future (2076–2100) under both SSP245 and SSP585 scenarios. Irrigation requirements are projected to decline by nearly 50 % across all future periods due to increased rainfall, except in the near future under SSP585 scenario, where no change is observed. For vertisols, the irrigation needs remain consistent at two supplemental irrigations across all periods. In contrast, for alfisols, the irrigation frequency currently 5 irrigations is projected to decrease by one in the near and mid-future under SSP245. These findings highlight the need for adaptive water management strategies to sustain maize production in Karnataka under changing climatic conditions.